Improving the Science Process Skills of STEM Students through Personality-based Approach - Leo Peter Dacumos (SEAQIS Journal of Science Education, 2021)
Scientific process skills (SPS) include skills that every individual could use in each step of his/her daily life by being scientifically literate and increasing the quality and standard of life by comprehending the nature of science (Aktamis and Ergin, 2008). The study aimed to investigate the impact of the Personality-based Approach (PBA) on the integrated science process skills (SPS) of grade 7 science, technology, and engineering (STE) students as compared to the conventional learning approach. A two-grouped quasi-experimental design with pretest and posttest was used in this study. This method consisted of two instructional groups (control group in conventional learning approach and experimental group in Personality-based Approach), and repeated testing (pretest and posttest) on students’ science process skill competency level. Results showed Grade 7 students of Baguio City National Science High School have an overall performance exceeding average achievement. Individually, the experimental group who was given the personality-based approach (PBA) performed high with their science process skills while the control group which was given with the conventional approach have typical science process skill levels. When compared, the experimental group have better performance in the skills where students are to prepare research proposals than their counterpart in the control group. However, in terms of the experimentation process down to creating models, the two groups do not differ.